Pemanfaatan Limbah Sayur Fermentasi sebagai Alternatif Pakan Ternak di Tinjau Melalui Tekstur dan pH Pakan - Jati, Putri Zulia; Zaki, M (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This research aims to determine the physical quality, texture and pH of vegetable waste fermented with EM4 liquid at different levels. The method used in this research was a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications, namely P0: Vegetable waste + 0% EM4, P1: Vegetable waste + 5% EM4, P2: Vegetable waste + 7% EM4, P3: Vegetable waste + 10% EM4. The variables measured include color, pH, aroma, and texture. The results of this research showed that the addition of EM4 liquid as a starter had a very significant difference (P<0.01) on the physical quality of color, aroma, texture, but had no effect (P>0.05) on the pH of the silage. The treatment that provides the best physical quality is the addition of P3: Vegetable waste + 10% EM4 assessed by color with an average value of 4.54 (yellowish green), pH with an average value of 5.53 (acid), average value of aroma 3.61 (typical acid). silage), as well as an average texture value of 2.64 (slightly soft).